Role and Determinants of Domestic Tourism Demand in Indonesia - Inda Dwi Setiawati; Widyastutik Widyastutik; Muhammad Firdaus (Economics Development Analysis Journal, 2023)
Tourism is a potential sector in the country's development strategy. Since the COVID-19 pandemic, Indonesian tourist visits have remained higher and more stable than foreign tourists. Domestic tourism is critical in defining an inward-looking national economic recovery strategy. However, few tourism studies still exist on the relationship between domestic tourism and regional economies. This study analyses the relationship between domestic tourism and Indonesia's regional economic growth and the determinants of Indonesian tourism demand in terms of domestic tourist expenditure. The data types used are secondary data provided by BPS, Kemenparekraf, Kemenkeu and Bank Indonesia. Analytical methods are the Granger causality test, fixed effect model and panel data regression analysis. The results show a one-way relationship between Indonesia's total tourism expenditure and regional economic growth. Based on research, the government's strategic priority is to increase domestic tourism expenditures by increasing per capita income, increasing tourist attraction and providing ATMs. ATMs facilitate the circulation of cash, influencing the increase in tourism expenditures. Stabilization of the consumer price index in tourist destinations should be maintained as it can negatively impact them.